Persistent Memory: A Survey of Programming Support and Implementations - Baldassin, Alexandro [UNESP]; Barreto, João; Castro, Daniel; Romano, Paolo (Association for Computing Machinery (ACM), 2022)
The recent rise of byte-addressable non-volatile memory technologies is blurring the dichotomy between memory and storage. In particular, they allow programmers to have direct access to persistent data instead of relying on traditional interfaces, such as file and database systems. However, they also bring new challenges, as a failure may render the program in an unrecoverable and inconsistent state. Consequently, a lot of effort has been put by both industry and academia into making the task of programming with such memories easier while, at the same time, efficient from the runtime perspective. This survey summarizes such a body of research, from the abstractions to the implementation level. As persistent memory is starting to appear commercially, the state-of-the-art research condensed here will help investigators to quickly stay up to date while also motivating others to pursue research in the field.
Keywords: failure-atomic sections; persistent heap; Persistent memory